Ideological Struggles and Identity Construction within the Politics of French Linguistics in Indonesia - Merry Andriani; Wening Udasmoro; Suhandano Suhandano (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
This article aims to analyse the ideological struggles reflected in the identity construction of French-language users in Indonesia. Using a critical sociolinguistic approach, it examines how Indonesians users, with their ideologies, adapt or adopt the French language and culture, as well as the different patterns and models they use to do so. The informants of this research consist of 9 students in deep interviews, 60 students in class observation, and 15 lecturers at 12 Indonesian universities who have taught the French language and culture for at least two years. Data from the interviews is compared to French instruction books and media discourses using intertextuality and interdiscursivity analysis. This research identifies three models used by French users in Indonesia: to adopt French language and culture, to adapt it, or to abstain from the reproduction of both. Users of the first model completely adopt all aspects of French culture, including in their consumption and style. Meanwhile, users of the second model tend to select and accept only those aspects considered positive within their own value system. Those using the final model tend to ignore many aspects of French culture and language.